1988
DOI: 10.1007/bf00540955
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of the benzodiazepine antagonist flumazenil (Ro 15-1788) on the performance of healthy subjects during experimentally induced ethanol intoxication

Abstract: Flumazenil is a specific benzodiazepine antagonist. This study was designed to determine whether it also reverses CNS depression due to acute alcohol intoxication. Intoxication was experimentally induced in 6 healthy volunteers by intravenous infusion of ethanol. Individual constant ethanol plasma concentrations in the range 1.47 +/- 0.04 g.l-1 to 1.71 +/- 0.03 g.l-1 were maintained over 6 h. Two doses of flumazenil (0.1 or 0.2 mg.kg-1) and placebo were administered intravenously in a randomized, double-blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Using low doses of alcohol (up to 0.04% BAC) no effects on psychomotor performance were reported [30,31]. At a BAC of 0.15%, Fluckinger et al [32] measured a marked impairment of psychomotor performance. It is not impossible that the effect of a steady-state BAC is smaller than on the ascending part of the BAC curve.…”
Section: Discussionmentioning
confidence: 99%
“…Using low doses of alcohol (up to 0.04% BAC) no effects on psychomotor performance were reported [30,31]. At a BAC of 0.15%, Fluckinger et al [32] measured a marked impairment of psychomotor performance. It is not impossible that the effect of a steady-state BAC is smaller than on the ascending part of the BAC curve.…”
Section: Discussionmentioning
confidence: 99%
“…If a patient fails to respond within 2 to 3 min after the end of injection it can be concluded that additional factors and circumstances other than benzodiazepines may be involved (Fantozzi et al 1988). In cases in which different sedative drugs contribute to the comatose state much higher doses have been reported to be necessary which, in single cases, far exceeded lOmg (Fantozzi et al 1988;Fluckiger et al 1988;Lheureux & Askenasi 1988a;Mapelli et al 1988). In successful cases, reinjections after 45 to 60 min are usually necessary to maintain the achieved state of vigilance.…”
Section: Dosage and Administrationmentioning
confidence: 95%
“…Before and after flumazenil administration, the volunteers had to undergo a battery of psychometric tests and subjective ratings of mood and performance. No improvement in the objective psychometric variables was observed (Fluckiger et al 1988). Thus, the effect of flumazenil in acute alcohol overdose remains unclear.…”
Section: Effectiveness In Alcohol or Nonbenzodiazepine Intoxicationmentioning
confidence: 95%
“…Так, антагонист БД-рецепторов Ro 15-1788 (флумазенил) неоднократно оценивался на предмет отрезвляющей активности. Результаты таких исследований оказались весьма противоречивыми [11][12][13]. Поэтому препарат не рекомендуется использовать при отравлениях этанолом тяжёлой степени.…”
unclassified